On the influence of graviny force on elastic wave processes in an ideal gas - Kouzov, Daniil Petrovich (Computational Continuum Mechanics, 2009)
The influence of gravity force on elastic wave processes in an ideal gas is considered. The simplest linear barotropic energetically closed model is used to describe for the description of such processes. Thus The wave equation gets acquires a linear correction term, which takes into account both the gravity force and the variation of gas density with height caused by it caused by it variation of gas density with height. Taking as examples typical wave processes (plane harmonic, spherical harmonic and nonstationary spherical waves) as examples, it is shown what changes this correction introduces to the analytic representations of these processes and how this is reflected in their character.
Keywords: ideal gas; perfect gas; wave processes; gravity force; barotropic model; gravitational correction; energy conservation law; plane wave; spherical harmonic wave; nonstationary spherical wave; cut-off frequency